2015
DOI: 10.1186/s11671-015-1008-y
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Atomic Layer Deposition of Zinc Oxide on Graphene

Abstract: The dissociation of zinc ions (Zn2+) from vapor-phase zinc acetylacetonate, Zn(C5H7O2)2, or Zn(acac)2 and its adsorption onto graphene oxide via atomic layer deposition (ALD) were studied using a quantum mechanics approach. Density functional theory (DFT) was used to obtain an approximate solution to the Schrödinger equation. The graphene oxide cluster model was used to represent the surface of the graphene film after pre-oxidation. In this study, the geometries of reactants, transition states, and products we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The ωB97X-D functional was used to calculate the UV-vis spectrum for a variety of possible structural defects in ZnO lattice grown on single layer graphene. The Spartan 14 quantum chemistry package (Wavefunction, USA) was used to perform all calculations in this study [ 21 , 22 ]. Equilibrium geometries were optimized by the B3LYP density functional method using the 6-311G** basis set; the developer of Spartan chose the Gaussian exponents for polarization functions to give the lowest energies for the modelled molecules.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ωB97X-D functional was used to calculate the UV-vis spectrum for a variety of possible structural defects in ZnO lattice grown on single layer graphene. The Spartan 14 quantum chemistry package (Wavefunction, USA) was used to perform all calculations in this study [ 21 , 22 ]. Equilibrium geometries were optimized by the B3LYP density functional method using the 6-311G** basis set; the developer of Spartan chose the Gaussian exponents for polarization functions to give the lowest energies for the modelled molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the 6-31G** basis set provides the p -type polarization functions for hydrogen. This can improve the total energy of the system along with the results for systems with large anions and can impose more flexibility [ 21 , 22 ]. Zn-containing structures were also optimized with larger basis sets and higher levels of theory [ 21 ], where all correction energies were calculated using the 6-311G**, 6-311++G** and 6-311++G(2df,2pd) basis sets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen in the figure, the electrostatic potential depends strongly on structure, as has been mentioned in our work. (75)(76)(77) We found that the transport time for electrons differs by about 10 orders of magnitude between nanorods and nanosphere clusters. (75) The use of graphene as an interface layer in the ZnO-decorated sensor is the main reason behind the sensitivity of the transport properties to the volumetric changes in the structures.…”
Section: Transport In Nanoporous Membranes Composite Electrodes Andmentioning
confidence: 95%
“…To the best our knowledge, zinc acetylacetonate [Zn­(acac) 2 ] has not been reported as a zinc source in experimental ALD studies, although it has been suggested in a computational study . Zn­(acac) 2 is nontoxic and stable in air, has a relatively low vapor pressure compared to DEZ, and exists as a solid at normal temperature and pressure. , In a recent study, Zn­(acac) 2 was used as a preferential chemical vapor deposition reactant to promote the Cu/Al 2 O 3 catalyst for hydrogenation of carbon dioxide to methanol .…”
Section: Introductionmentioning
confidence: 99%